Interventions and working relationships of voluntary organisations for diabetes self-management: a cross-national study - Portillo, Mari Carmen; Wensing, Michel (International journal of nursing studies, 2017)
Background: Diabetes has become a challenging health priority globally. Given the tensions of financially burdened health systems in Europe the mobilisation of community resources like voluntary organisations and community groups is seen as a health policy strategy to sustain the management of long-term conditions like diabetes. However, little is known about how this is happening in practice in Europe. Objectives: To explore diabetes self-management interventions undertaken or promoted by voluntary organisations and community groups in Europe; and describe the types of working relationships between these organisations, European health systems and users when implementing diabetes self-management programmes in different areas. Design: A mixed method study (survey/qualitative interviews) was undertaken. This research formed part of a European project (7th Framework programme of the European Commission) exploring the link between resources, like community organisations, and peoples’ capacities to manage long-term conditions. Settings: Six European countries (Bulgaria, Greece, Norway, Spain, the Netherlands and the United Kingdom) participated in the study. Three areas: deprived urban area, a relatively affluent urban area and a deprived rural area were purposefully selected. Participants: Through a purposeful sample and bottom up strategies 749 representatives of voluntary organisations and community groups were recruited from the geographical areas above. Organisations with at least three members, existing for at least one year that could provide information or other type of support directly or indirectly relevant to patients with diabetes were included. Methods: Participants completed a 15 item questionnaire for the survey (n=749) and a voice recorded semi structured interview (n=300). Data collection focused on the type of activities and roles developed to promote health, and relationships and communication channels between organisations, health services and users. Descriptive and comparative statistical and qualitative content analyses were used. Results: Participants perceived they had better reach of people with health needs than health providers, filled the administration gaps left in their capacity to deal with basic diabetes practical needs, humanized care, and acted as mediators between services and communities. There were significant differences between countries in relation to the types of activities (p-value<0.001), roles (p-value<0.001) and funding sources (p-value<0.001) of organisations concerning diabetes self-management. In non-affluent countries organisations tend to promote social activities twice more often. Conclusions: Community and voluntary organisations provide complimentary and on-going support in diabetes management. This involves a shift from focusing on the illness to also longing for social cohesion, sense of community and wellbeing in diabetes health practices and policies.